FUNGSI MANAJEMEN TERHADAP PENDIDIKAN ISLAM - Ruhaya, Besse (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
The management function of Islamic education is very important as well as the management function in education in general. Where the management of Islamic education orientation Islamic educational institutions managed by Islam also to achieve the objectives of Islamic education effectively and efficiently. Experts differ in formulating the management process, but in essence there are several similarities that include four management functions that must be considered, namely Islamic education planning, Islamic education organizing, implementation of Islamic education, and supervision of Islamic education. By paying attention to the four functions of education management above, it is expected to improve the overall quality of education.